A Systematic Review and Meta-Analysis of the Prevalence of Triplex Infections (Combined Human Immunodeficiency Virus, Hepatitis B Virus, and Hepatitis C Virus) among Pregnant Women in Nigeria - George Uchenna Eleje; Olabisi Morebise Loto; Hadiza Abdullahi Usman; Chinyere Ukamaka Onubogu; Preye Owen Fiebai; Godwin Otuodichinma Akaba; Ayyuba Rabiu; Ikechukwu Innocent Mbachu; Moriam Taiwo Chibuzor; Rebecca Chinyelu Chukwuanukwu; Ngozi Nneka Joe-Ikechebelu; Emeka Philip Igbodike; et al. (Obstetrics and Gynecology International, 2023)
Objective. We systematically identified the prevalence of triplex infections (combined human immunodeficiency virus (HIV), hepatitis B virus (HBV), and hepatitis C virus (HCV)) in pregnancy. Methods. To gather information on the frequency of triplex infections, we searched the databases of PubMed, CINAHL, and Google Scholar. Without regard to language, we utilized search terms that covered HIV, HBV, HCV, and pregnancy. Pregnant women with triplex infections of HIV, HBV, and HCV were included in studies that also examined the prevalence of triplex infections. Review Manager 5.4.1 was employed to conduct the meta-analysis. Critical appraisal and bias tool risk data were provided as percentages with 95% confidence intervals (95% CIs), and I2 was used as the statistical measure of heterogeneity. The checklist was created by Hoy and colleagues. The study protocol was registered on PROSPERO, under the registration number CRD42020202583. Results. Eight studies involving 5314 women were included. We identified one ongoing study. Pooled prevalence of triplex infections was 0.03% (95% CI: 0.02–0.04%) according to meta-analysis. Subgroup analysis demonstrated a significantly high prevalence of 0.08% (95% CI: 0.06–0.10%; 3863 women) in HIV-positive population than 0.00% (95% CI:−0.00-0.00; 1451 women; P<0.001) in general obstetric population. Moreover, there was a significant difference in the pooled prevalence between studies published between 2001 and 2010 and between 2011 and 2021 (0.14% (95% CI: 0.12 to 0.16 versus 0.03% (95% CI: 0.02 to 0.04%; P<0.001))) and participants recruited in the period between 2001 and 2011 and between 2012 and 2021 (0.13% (95% CI: 0.05 to 0.21; p=0.002 versus 0.00% (95% CI: −0.00 to 0.00%; p=1.00))), respectively. Conclusion. The combined prevalence of prenatal triplex infections was 0.03%, with rates notably higher among the group of pregnant women who were HIV-positive and during the recruitment period that took place before 2012. This prevalence still necessitates screening for these infections as necessary.